2022
DOI: 10.3390/machines10121143
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation of a Novel Low-Speed High-Torque Permanent Magnet Synchronous Motor with Asymmetric Stator Slots

Abstract: Focusing on the unstable electromagnetic performance of an air gap magnetic field caused by torque ripple and harmonic interference of a multi-slot and multi-pole low-speed high-torque permanent magnet synchronous motor (LHPMSM), an asymmetric stator slot is proposed to improve the comprehensive electromagnetic performance of the motor. Moreover, this paper develops an exact analytical model which predicts the magnetic field distribution based on Laplace’s and Poisson’s equations. The stator slot asymmetry is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In [16] and [21] it is suggested that modifying the tooth tips can improve the magnetic flux distribution and reduce saturation, improving the PMSM performance without affecting the manufacturability of the machine, e.g., the slot opening size remaining the same as in the symmetric geometry. The goal is to evaluate the impact of asymmetry on the PMSM performance, providing insights into optimizing PMSMs with tooth-coil windings for a high frequency and a high specific power.…”
Section: B Stator Tooth Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…In [16] and [21] it is suggested that modifying the tooth tips can improve the magnetic flux distribution and reduce saturation, improving the PMSM performance without affecting the manufacturability of the machine, e.g., the slot opening size remaining the same as in the symmetric geometry. The goal is to evaluate the impact of asymmetry on the PMSM performance, providing insights into optimizing PMSMs with tooth-coil windings for a high frequency and a high specific power.…”
Section: B Stator Tooth Geometrymentioning
confidence: 99%
“…Symmetric and asymmetric stator slots are compared in [21] to investigate the electromagnetic performance of a PMSM. According to the results, properly designed asymmetric stator teeth result in a higher fundamental flux density in the air gap, and therefore, a higher average torque.…”
Section: Introductionmentioning
confidence: 99%
“…The slot opening and the slot body for installing magnetic slot wedges comprise the asymmetric structure. As shown in Figure 4c, to facilitate modeling, the irregular region in the slot is simplified as the sector annular area and we define the asymmetry of the slot opening λ and the asymmetry of the inside slot ξ, which can be expressed as in [7].…”
Section: Modeling and Analysis Of Magnetic Fieldsmentioning
confidence: 99%
“…An Integrated LHPMSM for a mine hoist was proposed in [7]. The mechanical transmission structure of the motor does not adopt a reducer and coupling.…”
Section: Introductionmentioning
confidence: 99%
“…This consisted of computing the initial geometry and winding of the PMSM by using simple analytical equations and some general rules [59][60][61]. During this design stage, the iron core and permanent magnet volumes, the number of slots, the main sizes of the stator and rotor, the winding diagram and the number of turns, the materials to be used, etc., were estimated by the well-known relationships among the main machine sizes and other parameters [62][63][64][65].…”
Section: Pre-sizing the Pmsmmentioning
confidence: 99%